NIMG-28. CONVENTIONAL AND ADVANCED IMAGING FINDINGS FOLLOWING INTRACAVITARY DELIVERY OF AUTOLOGOUS CHIMERIC ANTIGEN RECEPTOR T-CELL THERAPY IN RECURRENT GLIOBLASTOMA. (5th November 2018) - Sahoo, Prativa; Badie, Behnam; Brown, Christine; Portnow, Jana; Chaudhry, Ammar; Kilpatrick, Julie; Rockne, Russell
Abstract: INTRODUCTION: Chimeric antigen receptor (CAR) T-cell therapy is an emerging area of immunotherapy for treatment of recurrent glioblastoma (GBM). However, evaluating response to CAR T-cell therapy is a considerable challenge. Radiologic changes following CAR T-cell therapy may include inflammation, which may be misinterpreted as disease progression, resulting in premature termination of the treatment. The iRANO criteria provides a 'limbo window' of up to six months from the start of immunotherapy during which radiologic worsening is tolerated while continuing immunotherapy. However, the time frame for identifying tumor progression following CAR T-cell therapy in the recurrent setting has not yet been characterized. AIM: Here we report imaging findings from conventional and advanced MRI sequences along with 18-FDG-PET-CT, acquired before, during, and after intracavitary administration of autologous central memory derived IL13Rα2-targeted CAR T-cell therapy for recurrent glioblastoma. METHODS: Imaging findings are reported from an ongoing dose-escalation study (NCT02208362) with maximum doses of 10x10 6 (dose schedule 1), 50x10 6 (dose schedule 2) and 100x10 6 (dose schedule 3) CAR T-cells. All patients underwent MRI scans on a 3T Siemens scanner prior to surgical debulking and CAR T-cell administration as well as at the end of each CAR T-cell treatment cycle, consisting of 3 CAR T-cell infusions into the resection cavity corresponding to time intervals of approximately 1 month. Conventional anatomic MRI included T1-weighted pre- and post-contrast, T2-spin echo, and T2-FLAIR sequences. Quantitative MRI included Dynamic Contrast Enhanced (DCE) Perfusion MRI and Diffusion Weighted Imaging (DWI). Additionally, patients underwent functional metabolic imaging with 18-FDG-PET-CT. Multiparametric imaging characteristics will be compared longitudinally before, during, and following CAR T-cell treatment and correlated to clinical progression. As of May 2018, 14 patients have been treated: dose 1 (n=3), dose 2 (n=3), dose 3 (n=8). Findings and analysis will be updated at the time of late-breaking abstract deadline.